Faktor-Faktor Yang Mempengaruhi Loyalitas Pelanggan Di Kopi Kenangan Bahu Kota Manado - Pangerapan, Angel Sharen; Kaunang, Rine; Waney, Nordy Fritsgerald Lucky (AGRI-SOSIOEKONOMI, 2024)
This research aims to analyze the factors influencing customer loyalty at Kopi Kenangan Bahu Kota Manado. The study was conducted from May to June 2023, and respondent selection was done randomly. Both primary and secondary data were utilized in the research. Primary data were collected through interviews based on questionnaires from 58 consumers at Kopi Kenangan Bahu Kota Manado. Secondary data were obtained from Kopi Kenangan Bahu and through relevant journal articles and theses related to the research topic, which is Factors Affecting Customer Loyalty. The research findings indicate that the quality of products and services at Kopi Kenangan Bahu does not significantly affect customer loyalty. On the other hand, promotions through social media, such as discount offers and loyalty programs, play a significant role in building and maintaining customer loyalty. The analysis results reveal that promotions have the highest coefficient value, indicating that this promotional strategy is a key factor that Kopi Kenangan Bahu should pay attention to in order to maintain a positive relationship with customers.